1989
DOI: 10.1159/000293578
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Adhesions in the True Pelvis after Pelviscopic Operative Treatment of Tubal Pregnancy

Abstract: 33 patients with tubal pregnancies, who had been treated by pelviscopy with organ preservation between 1978 until the beginning of 1988 have had follow-up examinations from within 4 months to 2 years after their first operation. In 15 (45%) of these 33 patients we found adhesions in the true pelvis on initial pelviscopy; these adhesions were lysed in all cases. During a second inspection of the abdominal cavity – either by laparotomy (Cesarean section; 4 patients) or by repelviscopy (29 patients) – mainly avas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…PID does not commonly present as a gynecologic emergency. Surgical indications for patients with PID include unsure diagnosis, failure of medical treatment, and rupture of a tuboovarian abscess (TOA).5 The 27 weeks, with the majority being in the late first and early second trimesters. In this review, the authors found 7 first-trimester spontaneous abortions, 2 congenital malformations, 2 pregnancies complicated by preterm labor, and 1 pregnancy complicated by preterm, premature rupture of membranes.…”
Section: Pelvic Inflammatory Diseasementioning
confidence: 99%
“…PID does not commonly present as a gynecologic emergency. Surgical indications for patients with PID include unsure diagnosis, failure of medical treatment, and rupture of a tuboovarian abscess (TOA).5 The 27 weeks, with the majority being in the late first and early second trimesters. In this review, the authors found 7 first-trimester spontaneous abortions, 2 congenital malformations, 2 pregnancies complicated by preterm labor, and 1 pregnancy complicated by preterm, premature rupture of membranes.…”
Section: Pelvic Inflammatory Diseasementioning
confidence: 99%